2014
DOI: 10.1007/s11274-014-1665-5
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide resistance of Botrytis cinerea in tomato greenhouses in the Canary Islands and effectiveness of non-chemical treatments against gray mold

Abstract: Tomato greenhouses in the Canary Islands, Spain, were surveyed to estimate frequencies of resistance to benzimidazoles, dicarboximides, anilinopyrimidines and N-phenylcarbamates in Botrytis cinerea. Resistance to carbendazim, iprodione, pyrimethanil and diethofencarb was found in 74.2, 86.4, 28.8 and 31.8% of isolates, respectively. Benzimidazole- and anilinopyrimide-resistant isolates were highly resistant, showing EC50 values above 500 µg/ml carbendazim and a mean EC50 value of 28.42 µg/ml pyrimethanil, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 38 publications
1
26
0
3
Order By: Relevance
“…Otherwise, the vacuma isolates had been previously reported as a predominant type in other host plants [37]. Additionally, we have found that all four isolate types, collected from different host plants, plant organs and locations, are fenhexamid-sensitive populations with a concentration between 0.013 -0.23 µg/ml indicating a fenhexamid sensitivity [48]. Thus, such fungicide concentration would be recommended as an effective fungicide against B. cinerea infections.…”
Section: Discussionmentioning
confidence: 57%
“…Otherwise, the vacuma isolates had been previously reported as a predominant type in other host plants [37]. Additionally, we have found that all four isolate types, collected from different host plants, plant organs and locations, are fenhexamid-sensitive populations with a concentration between 0.013 -0.23 µg/ml indicating a fenhexamid sensitivity [48]. Thus, such fungicide concentration would be recommended as an effective fungicide against B. cinerea infections.…”
Section: Discussionmentioning
confidence: 57%
“…With respect to fungicide resistance development, B. cinerea is considered as a classical 'high-risk' pathogen, and this complicates disease management programs (Elad et al 1992;Leroch et al 2011;Ma and Michailides 2005). Development of B. cinerea resistance to several classes of fungicides such as benzimidazoles, dicarboximides, phenylpyrroles, anilinopyrimidines, N-phenylcarbamates and succinate dehydrogenase inhibitors, has been reported worldwide (Bardas et al 2010;Elad et al 1992;Myresiotis et al 2007;Rodríguez et al 2014;Zhang et al 2009). Benzimidazole, dicarboximide and N-phenylcarbamates fungicides are no longer recommended as primary management tools because of widespread resistance of B. cinerea (Sun et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that B. cinerea can rapidly adapt to the environment and develop resistance, but it is susceptible to photosensitization (Luksiene, 2005;Luksiene, Paskeviciute, 2011). Benzimidazoles fungicides were introduced for plant disease control in the 1960's, but within a few years resistance emerged (Kretschmer, Hahn, 2008;Debieu et al, 2013;Rodríguez et al, 2014). Our research was carried out to test the new nonchemical measures reducing B. cinerea on berry fruits.…”
Section: Resultsmentioning
confidence: 99%
“…Our research was carried out to test the new nonchemical measures reducing B. cinerea on berry fruits. The photosensitization or volatile compound-based plant protection does not cause pathogen resistance (Neri et al, 2014;Rodríguez et al, 2014).…”
Section: Resultsmentioning
confidence: 99%